2011
DOI: 10.1007/s10934-011-9473-x
|View full text |Cite
|
Sign up to set email alerts
|

New hybrid materials based on layered double hydroxides and antioxidant compounds. Preparation, characterization and release kinetic studies

Abstract: New hybrid materials were obtained by intercalation of the antioxidant compounds vanillic acid and gallic acid in layered double hydroxides (LDHs) resulting formulations with controlled release and antioxidant activity. The hybrid materials were prepared by using two methods: coprecipitation and ion exchange. X-ray powder diffraction, infrared spectroscopy and thermogravimetric analysis confirmed that the antioxidant molecules were intercalated into interlayer spaces of LDHs. The release of the antioxidant com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 53 publications
3
23
0
1
Order By: Relevance
“…FL-R exhibited an analogous release pattern of FA to that of FA alone in good agreement with a prior work (Wang et al, 2009). On the contrary, FL-I and FL-E exhibited gradual and sustained release of FA in DW, consistent with previous reports (Zhang et al, 2006;Kong et al, 2010a,b;Silion et al, 2012). We next investigated time-dependent release profiles of FL nanohybrids in saline where release could be mediated by ion exchange.…”
Section: Release Pattern For Fa Eluting From Fl Nanohybridssupporting
confidence: 85%
See 1 more Smart Citation
“…FL-R exhibited an analogous release pattern of FA to that of FA alone in good agreement with a prior work (Wang et al, 2009). On the contrary, FL-I and FL-E exhibited gradual and sustained release of FA in DW, consistent with previous reports (Zhang et al, 2006;Kong et al, 2010a,b;Silion et al, 2012). We next investigated time-dependent release profiles of FL nanohybrids in saline where release could be mediated by ion exchange.…”
Section: Release Pattern For Fa Eluting From Fl Nanohybridssupporting
confidence: 85%
“…Thus, it is conceivable that different synthesis routes would result in different interlayer molecular arrangements, morphology, and release properties. It was reported that drug molecules stabilized in between LDH layers by either coprecipitation or ion-exchange were released through an initial burst followed by sustained release through intraparticle diffusion (Silion et al, 2012). Wang et al (2009) reported that an amoxicillin-LDH nanohybrid obtained by reconstruction exhibited an initial bursting effect due to the surfaceadsorbed moieties.…”
Section: Introductionmentioning
confidence: 99%
“…LDHs are excellent host matrices for storage and delivery of bioactive molecules and drugs, which are in this way protected against degradation by light, temperature, oxygen, alkali metals, etc. [22][23][24]25]. LDHs have been specifically used as nanocarriers of AOs, such as carnosine, gallic acid, vanillic acid, and ferulic acid [26,27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…LDHs have been specifically used as nanocarriers of AOs, such as carnosine, gallic acid, vanillic acid, and ferulic acid [26,27]. The intercalation between the layers protects the AO from oxidation during storage [22,24], reduces the effects of migration, and shows release behaviour suitable for their use in controlled delivery systems [22]. Similarly, trans-cinnamic derivatives (ferulic acid, cafeic acid, hydroxycinnamic acid), known as AOs and UV blockers, have been successfully entrapped between LDH layers for cosmetic use as UV sunscreens and UV stabilizers [28].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The structure of LDH is closely related to brucite-like layer, Mg(OH) 2 , where Mg 2+ is octahedrally surrounded by six OH -and share edges to form infinite sheet [14]. Some of the divalent ions are replaced by trivalent ions, resulting in positively charge sheet and compensated by anions in the interlayer galleries along with the water molecules [15][16][17].…”
Section: Introductionmentioning
confidence: 99%